2014
DOI: 10.1155/2014/764306
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Processing of Tungsten Heavy Alloys

Abstract: Tungsten heavy alloys (WHAs) belong to a group of two-phase composites, based on W-Ni-Cu and W-Ni-Fe alloys. Due to their combinations of high density, strength, and ductility, WHAs are used as radiation shields, vibration dampers, kinetic energy penetrators and heavy-duty electrical contacts. This paper presents recent progresses in processing, microstructure, and mechanical properties of WHAs. Various processing techniques for the fabrication of WHAs such as conventional powder metallurgy (PM), advent of pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 132 publications
(222 reference statements)
0
30
0
Order By: Relevance
“…Tungsten alloy was used to produce the elastic body. As listed in Table 1 [ 23 ], it offers high Young’s modulus and yield strength, which can help to increase the measuring range of the sensor. In addition, tungsten alloy also has a high melting point and low coefficient of thermal expansion (CTE), which can help the sensor work at high temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Tungsten alloy was used to produce the elastic body. As listed in Table 1 [ 23 ], it offers high Young’s modulus and yield strength, which can help to increase the measuring range of the sensor. In addition, tungsten alloy also has a high melting point and low coefficient of thermal expansion (CTE), which can help the sensor work at high temperature.…”
Section: Methodsmentioning
confidence: 99%
“…WHAs are used in radiation shields, kinetic energy penetrators, counterbalances, vibration dampers, and rocket nozzles. A good review paper on WHAs can be found in [41].…”
Section: Introductionmentioning
confidence: 99%
“…WHAs generally have fairly good room to high-temperature tensile strength and ductility [28][29][30][31][34][35][36][39][40][41]. However, the key limiting structural property for W and W-alloys is usually fracture toughness and a high brittle to ductile transition temperature (BDTT) [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten-based composites are always processed through powder metallurgy using element powders [6]. However, this may be not a feasible method to fabricate WeNiTi composites because of the composition sensitivity of martensitic transformation of NiTi alloys.…”
Section: Introductionmentioning
confidence: 99%